LATE TRIASSIC (LATE NORIAN-RHAETIAN) RADIOLARIANS FROM THE ANTALYA NAPPES, CENTRAL TAURIDES, SOUTHERN TURKEY (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2002)
The Hocaköy section measured from the Alakirçay Nappe (middle nappe) of the Antalya Nappes contain rich radiolarian fauna ranging from late Norian (Late Triassic) to middle-late Cenomanian (mid Cretaceous). At the basal part of the section, the Late Triassic (late Norian-Rhaetian) Gökdere Formation is characterized by gray to beige cherty limestone at the base and pinkish red chert- gray to beige limestone alternation at the top, with moderately to well-preserved radiolarians in the red chert beds. The overlying Jurassic - Middle Cretaceous Hocaköy Radiolarite is mainly represented by chert-mudstone alternations with some limestone interlayers. Radiolarians of the Gökdere Formation can be well correlated with that of the fauna from the Mino Terrane, central Japan and the fauna from the Queen Charlotte Islands, British Columbia, Canada. Four radiolarian zones from central Japan are recognized in the fauna obtained from Gökdere Formation such as “Praemesosaturnalis multidentatus Lowest Occurrence Zone (TR8A)” (late Norian), “Praemesosaturnalis pseudokahleri Lowest Occurrence Zone (TR8B)” (late Norian), ? “ Skirt F lowest Occurrence Zone (TR8C)” (late Norian-Rhaetian) and partly “Haeckelicyrtium breviora Taxon Range Zone (TR8D)” (Rhaetian). In comparison with the Queen Charlotte fauna, the two zones “Betraccium deweveri Zone” (late Norian) and “Proparvicingula moniliformis Zone” (early Rhaetian) are also encountered in the Gökdere Formation. Radiolarians of the uppermost part of the Gökdere Formation indicate that “Globolaxtorum tozeri Zone” defined in Queen Charlotte Islands corresponding to the late Rhaetian, is not present in the section. Five new taxa, Capnuchosphaera okayi, Bistarkum rhaeticum, Praemesosaturnalis heilongjiangensis aksekiensis, P. nobleae, Veghicyclia sanfilippoae were determined within the late Norian-Rhaetian radiolarian fauna of the Gökdere Formation in Hocaköy section.